Pengaruh Work-Life Balance dan Affective Commitment Terhadap Kinerja Karyawan Dengan Job Stress Sebagai Variabel Mediasi (Studi Pada Apoteker di Wilayah Sidoarjo) - Novelia Agustina Wandagu; Faidal Faidal (Management Department of Economics and Business Of Trunojoyo Madura University, 2026)
This study aims to analyze the effect of work-life balance and affective commitment on employee performance with job stress as a mediating variable among pharmacists in the Sidoarjo region. The study used a quantitative approach with an explanatory research method. Data were obtained by distributing questionnaires to 100 pharmacists working in pharmacies, clinics, hospitals, community health centers, and the pharmaceutical industry in Sidoarjo Regency using a purposive sampling technique. Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4. The results showed that work-life balance and affective commitment had a significant positive effect on employee performance, and a significant negative effect on job stress. Job stress also had a significant negative effect on employee performance and was proven to partially mediate the effect of work-life balance and affective commitment on performance. This study concluded that improving work-life balance and affective commitment can reduce work stress, thereby improving pharmacist performance. Organizations are advised to implement policies that support work-life balance, strengthen employee commitment, and manage work stress sustainably to improve the quality of pharmaceutical services.